2020
DOI: 10.1130/b35421.1
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic evolution of strike-slip zones on continental margins and their impact on the development of submarine landslides (Storegga Slide, northeast Atlantic)

Abstract: Submarine landslides have affected the mid-Norwegian margin since the Last Glacial Maximum. However, the role of tectonic movements, and most especially fault reactivation, in generating landslides offshore Norway is largely unconstrained. This study uses high-quality three-dimensional seismic and borehole data to understand how landslide development is controlled by faults propagating within the uplifted south Modgunn arch. Variance and structural maps above the south Modgunn arch show that: (1) local scarps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Nevertheless, Song et al. (2020) also observed that the fossilised Opal A‐CT traces the distribution of the deep, 50 km sill on the eastern flank of the Modgunn Arch and suggested a spatial correlation between the location of the intrusion and the Opal A‐CT reflection. If renewed magmatic input was associated with the reactivation of the Jan Mayen Corridor, enhanced heat flow via conduction could have fossilised the Opal A‐CT transition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, Song et al. (2020) also observed that the fossilised Opal A‐CT traces the distribution of the deep, 50 km sill on the eastern flank of the Modgunn Arch and suggested a spatial correlation between the location of the intrusion and the Opal A‐CT reflection. If renewed magmatic input was associated with the reactivation of the Jan Mayen Corridor, enhanced heat flow via conduction could have fossilised the Opal A‐CT transition.…”
Section: Discussionmentioning
confidence: 99%
“…In these areas, the Nise Formation is assumed to be present but it was not seismically interpreted (Figure 3). Thickness variations occur in the Tare Formation due to differential compaction over intrusion‐related structures (Kjoberg et al., 2017; Song et al., 2020). Thus, the regional unconformity at the top of the Top Tang Formation (late Paleocene) was used as a reference horizon for interpreting the relative ages of the hydrothermal vent complexes (Figure 1c).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, multibeam bathymetry data are now routinely used to characterize the morphological expression of failures and associated deposits (e.g., Hill et al, 2020; Watson et al, 2020), seismic reflection data are used to map the substrate architecture of failure zones (e.g., Berndt et al, 2012; Brothers et al, 2018), and measurements from seafloor drilling/coring provide constraints on geotechnical parameters and the age of sedimentary units involved in the failure process (e.g., Ikari et al, 2011; Kremer et al, 2017). Studies focused on incipient failure or on preconditioning factors have been conducted along many margins around the world (e.g., Bryn et al, 2005; Kvalstad et al, 2005; Piedade et al, 2018; Song et al, 2020), including regions undergoing compressional tectonics and uplift (e.g., Alves et al, 2014; Gee et al, 2007; Gross et al, 2018; Ikari et al, 2011); however, such studies are limited along the U.S. West Coast.…”
Section: Introductionmentioning
confidence: 99%
“…2‐D seismic reflection data provide a starting point for interpretations of regional framework geology but often fall short in providing the detail needed to characterize the along‐strike variations in structure and stratigraphy that may be contributing to slope instability. 3‐D seismic reflection data allow for more accurate mapping of faults, folds, and sedimentary packages but also make it possible to quantify vertical and lateral variations of substrate features through the use of detailed 3‐D horizon mapping and seismic attribute calculations (e.g., Edwards et al, 2018; Gross et al, 2018; Song et al, 2020). The public release of industry 3‐D seismic reflection data sets and the collection of new high‐resolution 2‐D multichannel seismic reflection (MCS) data in the western Santa Barbara Channel (SBC; Figures 1 and 2) provide new opportunities to study the factors that contribute to slope instability in a region characterized by active tectonics and Quaternary submarine landslides.…”
Section: Introductionmentioning
confidence: 99%